Đề xuất khung tham chiếu tích hợp năng lực số và năng lực trí tuệ nhân tạo cho giảng viên, cán bộ quản lí cơ sở giáo dục đại học tại Việt Nam - Lê Phước Sơn, Lê Phước Sơn; Trần Thúy Hiền Trần Thúy Hiền (Tạp chí Giáo dục, 2026)
In Vietnam, there is currently a Digital Competency Framework for learners and a set of indicators for evaluating the digital transformation of higher education institutions. However, an integrated reference framework for digital and artificial intelligence (AI) competencies for lecturers and administrators in higher education institutions has not yet been established. Thisleadsto a lack of a unified basisforstandardizing, evaluating, recruiting, and training personnel to serve digital transformation. Based on document analysis and comparison with typical international frameworks, combined with a review of domestic policy tools, this paper proposes an integrated reference framework for digital and AI competencies for lecturers and administrators in higher education institutions in Vietnam, comprising 7 competency domains and 3 levels of proficiency. A novel aspect of this paper is the proposal of an integrated reference framework designed as a "CoreCustomized" framework (a minimum common core and expansion modules based on roles), unlike previous studies which separated digital and AI competencies or failed to define a "minimum core" for implementation at the institutional level.